13 Steps to Manufacturing in China - Mitchell, B. author. aut Link
384 p.
Keywords: A comprehensive reference book providing the tactics, strategies, and methodology for establishing a manufacturing plant in China. The book is jam packed with details including sourcing Chinese equipment, importing used or new equipment, building construction, and permit requirements.